Survive, Sustain And Succeed During Subsistence Crises- A Cluster Study Of Buddhist Handloom Weavers' Of Odisha - et. al., Mr. Samira Patra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Like Foods and Shelters, clothes are the most important primary elements of human life. The clothes or handloom products identity the look of civilized human society. The Buddhist handloom weavers are those weavers who are the followers of Buddhism as well as the weavers of different kinds of handloom products. These handloom products are primarily used for the Buddhist monk in the period of Lord Buddha. Since that time production of handloom products are the lifeline of the Buddhist Weavers’ and provide permanent employment to them. There are various types of raw materials required for the production of handloom products which are imported from the different parts of the state as well as the country. During Subsistencecrises period like lockdown due to COVID-19, these inputs are scarce and not at easy reach for the process of production.In the other hand, during thecrises period, handloom products could not get marketed by the weavers and hence money is not circulated for smooth sailing of theircost of living. In both the aspects, Buddhist handloom weavers are not getting their earnings for theirfinancial need and hence, it is difficult for them to survive and sustain. Research Gap: No remarkable studies have been conducted onsurvival, sustainance and succeed of the Buddhist handloom weavers during subsistence crises in the study area i.e. in the Cuttack District. Objective:This is an attempt to study the Survive, Sustain and Succeed scenario ofBuddhist handloom weavers of Odishaduring subsistence Crises. Research Methodology: 4.1. Nature and Sources of Data (with Sample Size):The study is based on primary data. The primary data have been collected through well design questionnaire and indirect interviews. The sample data consists of 100 Buddhist handloom weavers’ respondents. 4.2. Tools of Analysis:There are various tools like percentage calculations; valid percentage calculation, chi-square test, correlation have been used for analysis and interpretation of results. 5.Conclusions:The present study concluded that it is very difficult to survive, sustain and succeed during for the Buddhist handloom weavers’ during subsistence crises like COVID-19 without govt. support.